INOVASI VIETNAM DRIP PADA PRODUK RORO COFFE BESOWO - muhammad akmal auli akmal auli; Muhammad Hazim Munshif Hazim; Novia Ayu Anggraeny Novia; Retno Ayu Wulandari Retno; Dwi Anggraini Setya Putranti anggi (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2023)
The aim of this service is to innovate products at Roro Coffee by adding the Vietnam Drip variant to the coffee powder packaging. It is hoped that the Vietnam Drip model variant as one of Roro Coffee's products can expand market segmentation and build a broad economic network on social media. This service uses the ABCD approach with the steps Discovery, Dream, Design, Define and Destiny. The result is that the goal of innovation is to follow trend developments, find new, more competitive markets, retain old customers by strengthening new products, and increase the selling power of Roro Coffee. Vietnam Drip appears in box or box packaging which has 2 variants, namely 10 and 5 sachet variants with competitive prices.